Нужно подробное решение. tgx=0 ctg(3п/2-x)=-1 tg(x-п)=sqrt3 tg2x=-sqrt3 tgx=-2/3 tg(2x+п/6)=sqrt3/3

fianketo05 fianketo05    2   21.06.2019 21:40    0

Ответы
sashatitsky sashatitsky  17.07.2020 10:16
Tgx =0 ⇒ x=0
ctg(3π/2-x)=-1  ⇒  3π/2-x=-π/4
                           x=π/4+3π/2=7π/4

tg(x-π)=√3  ⇒   x-π=π/3
                         x=π/3+π=4π/3
 tg2x=-√3   ⇒   2x=-π/3    
                        x=-π/6
tgx=-2/3  ⇒  x=arctg(-2/3)=-arctg2/3
tg(2x+π/6)=√3/3  ⇒   2x+π/6=π/6
                              2x=0 x=0
ПОКАЗАТЬ ОТВЕТЫ